The incidence of HPV infection in anal cancer patients in Greece - Alexandrou, A; Dimitriou, N; G Levidou; Griniatsos, J; Sougioultzis, S; P Korkolopoulou; Felekouras, E; Pikoulis, E; Diamantis, T; Tsigris, C; Tzivras, M (Acta Gastroenterol Belg, 2014)
Background and aim of the study : Although anal cancer represents a relatively uncommon malignancy, its incidence over the last five decades, has been reported as increased for both sexes, worldwide. Human papillomavirus (HPV) infection has been shown to be a major cause for its development. The aim of the present study is to report on clinical, epidemiological and virological data of squamous anal cancer in Greek patients. Patients and Method : Between January 2002 and December 2010, 11 Greek patients (6 females) who were diagnosed as suffering from squamous cell anal or perianal cancer, were treated in our Hospital. Formalin fixed paraffin embedded tissue samples, obtained at the time of the anal biopsy or surgery, were analyzed by PCR in order to identify the presence as well as the type of HPV infection. Results : Overall, the presence of HPV DNA was detected in 6 out of the 11 patients (54.5%). The “highrisk” HPV DNA was  detected in 3 of them (2 women and 1 man), while the “lowrisk” HPV DNA was detected in the remaining three (2 women and 1 man). Conclusion : The incidence of HPV infection in squamous cell anal cancer Greek patients, is lower than other Western countries, probably reflecting differences in sexual habits in the Greek  population